2008
DOI: 10.1111/j.1538-7836.2007.02882.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal corticotrophin-releasing hormone mRNA, but not phosphatidylserine-exposing microparticles, in maternal plasma are associated with factor VII activity in pre-eclampsia

Abstract: To cite this article: Freeman DJ, Tham K, Brown EA, Rumley A, Lowe GD, Greer IA. Fetal corticotrophin-releasing hormone mRNA, but not phosphatidylserine-exposing microparticles, in maternal plasma are associated with factor VII activity in pre-eclampsia. J Thromb Haemost 2008; 6: 421-7Summary. Background: Pre-eclampsia is associated with increased placental debris circulating in maternal plasma. Objectives: This study related placental debris to maternal markers of coagulation and endothelial activation in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
5
19
1
Order By: Relevance
“…Placental corticotrophin-releasing hormone RNA and microparticles in maternal plasma are not measures of placental shedding of debris: reply to a rebuttal We agree with Buimer et al [1] that the total number of microparticles in maternal plasma is not a measure of placental shedding of debris. We made our view clear in the discussion of our article [2] that Ôthe total microparticle population (in maternal plasma) comprises a mixture of fetal and maternalderived microparticles and is not a specific marker of placental debris.Õ We did not claim that the overall procoagulant activity of total microparticles was specific for placenta-derived microparticles and stated Ôour prothrombinase assay would detect total PS-exposing microparticles and would be unable to distinguish between fetal and maternal-derived material.Õ While the letter of Buimer et al [1] refers to our study as measuring the number or concentration of microparticles, this is not the case. Our interest in microparticle prothrombinase activity, and fetal CRH mRNA, in maternal plasma was in their interaction with the maternal coagulation system.…”
Section: Disclosure Of Conflict Of Interestssupporting
confidence: 65%
See 1 more Smart Citation
“…Placental corticotrophin-releasing hormone RNA and microparticles in maternal plasma are not measures of placental shedding of debris: reply to a rebuttal We agree with Buimer et al [1] that the total number of microparticles in maternal plasma is not a measure of placental shedding of debris. We made our view clear in the discussion of our article [2] that Ôthe total microparticle population (in maternal plasma) comprises a mixture of fetal and maternalderived microparticles and is not a specific marker of placental debris.Õ We did not claim that the overall procoagulant activity of total microparticles was specific for placenta-derived microparticles and stated Ôour prothrombinase assay would detect total PS-exposing microparticles and would be unable to distinguish between fetal and maternal-derived material.Õ While the letter of Buimer et al [1] refers to our study as measuring the number or concentration of microparticles, this is not the case. Our interest in microparticle prothrombinase activity, and fetal CRH mRNA, in maternal plasma was in their interaction with the maternal coagulation system.…”
Section: Disclosure Of Conflict Of Interestssupporting
confidence: 65%
“…Fetal corticotrophin-releasing hormone mRNA, but not phosphatidylserine-exposing microparticles, in maternal plasma are associated with factor VII activity in pre-eclampsia. The interesting article by Freeman et al [1] reports an association between F-VII activity and corticotrophin-releasing hormone (CRH) mRNA but not number of circulating microparticles (MP) in pre-eclamptic patients. Their findings depend on the presumption that fetal CRH mRNA and number of MP are measures of placental shedding of debris.…”
mentioning
confidence: 99%
“…There have been many reports of increased circulating levels of tissue factor in pre-eclamptic women [29], [31], [33]–[35] but these measurements have all been made using immunological methods or poorly standardized functional assays, resulting in values several orders of magnitude higher than those obtained by specific functional assays. As subpicomolar quantities of tissue factor are now known to initiate clotting, it is highly unlikely that these measurements were detecting active tissue factor.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated components of the TF-dependent pathway in preeclamptic women, but results are inconsistent [6][7][8][9][10][11][12][13][14][15][16][17][18]. Recently we assessed the value of measuring the TF-dependent coagulation factors in white women with severe P-EC and suggested that plasma FVII levels can differentiate women with P-EC from healthy nonpregnant women or normal pregnant women at the same trimester, with high sensitivity, specificity, positive and negative predictive values [19].…”
Section: Introductionmentioning
confidence: 99%